2022
DOI: 10.1513/annalsats.202012-1544oc
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease in Adults Exposed to Fine Particles from a Coal Mine Fire

Abstract: Introduction. In 2014 the Hazelwood open cut coal mine burned for six weeks, exposing nearby residents to fine particulate matter (PM2.5). The long-term health consequences are being evaluated as part of the Hazelwood Health Study (HHS). These analyses explore the association between PM 2.5 and chronic obstructive pulmonary disease (COPD).Methods. A sample of 346 exposed, and 173 unexposed, adults participated in the longitudinal Respiratory Stream of the HHS. Participants underwent spirometry and gas transfer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The one exception was the fire-related PM 2.5 model, in which we detected increases in emergency presentations overall and among women and younger persons. Previous Hazelwood Health Study analyses consistently found long-term increases in respiratory symptoms (29,40,41), as well as medium-term increases in emergency department presentations for respiratory conditions (13,14) and poorer lung function in relation to smoke exposure (42). However, recent analysis suggests that the effects on lung function have attenuated over time (43), possibly indicating recovery.…”
Section: Discussionmentioning
confidence: 91%
“…The one exception was the fire-related PM 2.5 model, in which we detected increases in emergency presentations overall and among women and younger persons. Previous Hazelwood Health Study analyses consistently found long-term increases in respiratory symptoms (29,40,41), as well as medium-term increases in emergency department presentations for respiratory conditions (13,14) and poorer lung function in relation to smoke exposure (42). However, recent analysis suggests that the effects on lung function have attenuated over time (43), possibly indicating recovery.…”
Section: Discussionmentioning
confidence: 91%
“…The stronger and occasionally significant associations between PM 2.5 and symptom identified COVID‐19 cases could be due to cough being an outcome of both PM 2.5 exposure and COVID‐19 22–24 . Participants whose cough increased due to the coalmine fire would therefore be at higher risk of misclassification of COVID‐19, resulting in an artificial association with PM 2.5 .…”
Section: Discussionmentioning
confidence: 99%
“…Symptom‐identified cases were based on a standardized rubric that identified likely COVID‐19 cases based on a set of symptoms experienced in 2020, 2021 and each month in 2022, and participant demographics 21,22 . While the symptom‐based rubric was used to identify undiagnosed and unreported cases, there was a potential for misclassification due to one of the symptoms, cough, also being an outcome of PM 2.5 exposure 23,24 ; the implications are covered in the Discussion. More information about the COVID‐19 indicators can be found in Appendix S1 in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…and chronic cough and current wheeze up to 8.5 to 9 years after mine fire [9]. Between 3.5 to 4 years after the mine fire dose-response relationships were observed between PM2.5 and spirometry consistent with chronic obstructive pulmonary disease (COPD) in adult non-smokers [10].…”
Section: Introductionmentioning
confidence: 99%